The Phillips Curve, the Persistence of Inflation, and the Lucas Critique: Evidence from Exchange-Rate Regimes: Comment - Kool, Clemens J. M; Lammertsma, Alex (American Economic Review, 2000)
The Phillips Curve, the Persistence of Inflation, and the Lucas Critique: Evidence from Exchange-Rate Regimes: Comment by Clemens J. M. Kool and Alex Lammertsma. Published in volume 90, issue 1, pages 312-315 of American Economic Review, March 2000